Syntheses of Optically Active V‐Shaped Molecules: Relationship Between their Chiroptical Properties and the Orientation of the Stacked π‐Electron System. Issue 41 (4th November 2021) - Asakawa, Ryo; Tabata, Daiki; Miki, Nanami; Tsuchiya, Motoki; Inoue, Ryo; Morisaki, Yasuhiro
Abstract: Two kinds of optically active V‐shaped molecules were synthesized from enantiopure disubstituted and tetrasubstituted [2.2]paracyclophane as chiral building blocks. The p‐ arylene‐ethynylene‐type π‐electron systems in these species were stacked at an angle of 60°, and although the two molecules consisted of the same π‐electron system, the orientations of these systems were different. In addition, their optical properties were almost identical, while in contrast, significant differences were observed between their chiroptical properties. It was therefore suggested that circularly polarized luminescence behavior could be controlled by adjusting the orientation of the stacked π‐electron systems. Abstract : Two kinds of optically active V‐shaped molecules were synthesized from enantiopure [2.2]paracyclophane as chiral building blocks. Although the two molecules consisted of the same π‐electron system, the orientations of the stacked π‐electron systems were different. Circularly polarized luminescence behaviors could be controlled by adjusting their orientation.